2007
DOI: 10.1186/1749-8090-2-15
|View full text |Cite
|
Sign up to set email alerts
|

Safe wrapping of the borderline dilated ascending aorta during aortic valve replacement

Abstract: Background: Techniques of reduction aortoplasty are widely published in the literature with conflicting results. External support seems to be an important factor in preventing recurrence but, in some cases, this technique caused erosion of the aorta because of the wrinkles the prosthesis creates in the rear side of the aorta.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 8 publications
0
7
0
2
Order By: Relevance
“…In order to prevent the formation of folds it is essential to adequately measure the necessary length of the graft and to apply the correct longitudinal tension. As an alternative to a straight graft, Tappainer et al proposed the creation of a slightly curved tubular support made up of two segments of a straight vascular prosthesis (21).…”
Section: Wrapping Techniquementioning
confidence: 99%
“…In order to prevent the formation of folds it is essential to adequately measure the necessary length of the graft and to apply the correct longitudinal tension. As an alternative to a straight graft, Tappainer et al proposed the creation of a slightly curved tubular support made up of two segments of a straight vascular prosthesis (21).…”
Section: Wrapping Techniquementioning
confidence: 99%
“…Аортопластику можно дополнять обертыванием ВА участком сосудистого протеза для укрепления стенки аорты [30]. Несмотря на определенную дискутабельность, ряд исследователей приводят данные в пользу безопасности, эффективности редукционной пластики и/или наружного обертывания ВА и о низком числе отдаленных осложнений [15,25,31,32]. Некоторые исповедуют персонифицированный подход к коррекции сопутствующего расширения ВА при протезировании ДАК [33].…”
Section: Discussionunclassified
“…In general, surgery with concomitant cardiovascular procedures especially involving the aortic valv 4 borderline dilated distal ascending aortae with a felt or prosthetic graft to prevent dilation over the long term. Some reports have indicated that wrapping effectively preserves dilated ascending aortae [2][3][4]. However, we recently experienced a need to re-operate on a replaced distal ascending aorta of a male patient that had become dilated despite being wrapped with a prosthetic graft (Figure 4).…”
Section: Discussionmentioning
confidence: 99%